Characteristics of a Brazilian prototype of Dialectical Behavior Therapy (DBT) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The aim of this study was to develop and characterize a Brazilian Dialectical Behavior Therapy (DBT) prototype to be used in future process and process-outcome studies in this approach. Therefore, 10 Brazilian experts in DBT answered a sociodemographic questionnaire and ordered the 100 items of the Psychotherapy Process Q-Set (PQS) according to what they considered to be an ideal session in this psychotherapy. There was a high level of agreement among participants (α = 0.94), and the Q-type principal components analysis differentiated the DBT prototype from the prototypes of other approaches used for comparison. Correlations were identified between the different psychotherapeutic models analyzed, fostering discussion about common factors and the heterogeneous nature of DBT and the Brazilian sample of experts. These results allow the prototype developed to be used in investigations of the multiple variables present in the therapeutic process of this treatment model.